2012
DOI: 10.5334/jbr-btr.719
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial essay: Multidetector CT of hepatic artery pathologies

Abstract: Imaging of the visceral vascular structures non-invasively with the development of MDCT is one of the most important forward leaps in radiology in the last decade. With the improvement of the MDCT technology any arterial and venous vascular structure of the abdomen can be easily detected and treatment planning can be done in a straightforward manner. Compared to conventional catheter angiography, MDCT imaging of the vascular tree is sometimes more contributory to the patient's treatment plan. Pathologies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…MDCT in combination with CPR analysis was quite sensitive to identify stenosis of the RPHA, and atherosclerosis was confirmed by IVUS. Because it has been reported that atherosclerosis of the hepatic artery is related to arterial dissection, aneurysm, and thrombosis [ 5 ], we performed prophylactic stent placement to prevent postoperative arterial complications. Although the diagnostic and therapeutic procedures were successful, the patient suffered from multiple pyogenic liver abscesses 4 months after liver surgery.…”
Section: Discussionmentioning
confidence: 99%
“…MDCT in combination with CPR analysis was quite sensitive to identify stenosis of the RPHA, and atherosclerosis was confirmed by IVUS. Because it has been reported that atherosclerosis of the hepatic artery is related to arterial dissection, aneurysm, and thrombosis [ 5 ], we performed prophylactic stent placement to prevent postoperative arterial complications. Although the diagnostic and therapeutic procedures were successful, the patient suffered from multiple pyogenic liver abscesses 4 months after liver surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It can be detected during routine abdominal CT performed during the follow-up of this group of patients. We read the article titled as 'Multidetector CT of hepatic artery pathologies' by Karaosmanoglu et al (1), published in JBR-BTR (95: 345-349, 2012) with a great interest. This article will be a useful guide for radiologists in their future experiences.…”
mentioning
confidence: 99%